How to (or not to) integrate vertical programmes for the control of major neglected tropical diseases in sub-Saharan Africa. - Narcis B Kabatereine; Mwele Malecela; Mounir Lado; Sam Zaramba; Olga Amiel; Jan H Kolaczinski (Public Library of Science (PLoS), 2010)
Combining the delivery of multiple health interventions has the potential to minimize costs and expand intervention coverage. Integration of mass drug administration is therefore being encouraged for delivery of preventive chemotherapy (PCT) to control onchocerciasis, lymphatic filariasis, schistosomiasis, soil-transmitted helminthiasis, and trachoma in sub-Saharan Africa, as there is considerable geographical overlap of these neglected tropical diseases (NTDs). With only a handful of countries having embarked on integrated NTD control, experience on how to develop and implement an efficient integrated programme is limited. Historically, national and global programmes were focused on the control of only one disease, usually through a comprehensive approach that involved several interventions including PCT. Overcoming the resulting disease-specific structures and thinking, and ensuring that the integrated programme is embedded within the existing health structures, pose considerable challenges to policy makers and implementers wishing to embark on integrated NTD control. By sharing experiences from Uganda, Tanzania, Southern Sudan, and Mozambique, this symposium article aims to outlines key challenges and solutions to assist countries in establishing efficient integrated NTD programmes.